Bacteriuria. Cochrane Database Syst Rev. 2015;4:CD009534. - Bigotte Vieira, Miguel (2018)
Asymptomatic bacteriuria is frequently detected in women aged up to 60 years, patients with diabetes and elderly patients. The benefit of antibiotic treatment for this condition is controversial. The objective of this Cochrane systematic review was to assess the effectiveness and safety of antibiotic treatment for asymptomatic bacteriuria in adults. A systematic review of the literature up to 24 February 2015 was performed using the Cochrane Renal Group’s Specialised Register. Randomised controlled trials (RCTs) and quasirandomised controlled trials comparing antibiotics to placebo or no treatment for asymptomatic bacteriuria in adults were included. The outcomes of interest were the development of symptomatic urinary tract infection, complications, death, adverse events, development of antibiotic resistance, bacteriological cure, and decline in kidney function. Nine studies (1614 participants) were included in this review. The incidence of symptomatic urinary tract infection, complications or death was similar between groups. Antibiotic use was significantly associated with bacteriological cure and an increase in minor adverse events. No decline in kidney function was observed with any one of the treatments. According to the results of the studies included in this revision, authors have concluded that there is no clinical benefit in treating asymptomatic bacteriuria in adults.